Relational Religion Fires as Confidants in Parsi Zoroastrianism - Naasen Tandberg, Håkon (2019)
Håkon Naasen Tandberg explores how, when, and why humans relate to the non-human world. Based on two ethnographic fieldworks among the Parsis in Mumbai, the research focuses on the role of temple fires in the lives of present-day Parsi Zoroastrians in India as an empirical case. Through four ethnographic portraits, the reader will get a deeper look into the lives of four Parsi individuals, and how their individual biographies, personalities, and interhuman relationships, along with religious identities and roles, shape-and to a certain extent are shaped by-their personal relationships with non-human entities. The book combines affordance theory, exchange theory, and social support to analyze such relationships, and offers suggestive evidence that relationships with non-human entities-in this case the Zoroastrian temple fires-can be experienced as no less real, important, or meaningful than those with other human beings.